Can the neutrophil/lymphocyte ratio (NLR) have a role in the diagnosis of coronavirus 2019 disease (COVID-19)? - Nalbant,Ahmet (2020)
SUMMARY OBJECTIVE The present study aimed to investigate the role of neutrophil/lymphocyte ratio (NLR), an inflammation marker, complete blood count, and biochemical parameters in the diagnosis of COVID-19. METHODS A total of 80 patients who had been hospitalized in the internal medicine clinic were enrolled in the study. The cases were allocated into two groups, i.e., COVID (+) and (-), based on real-time reverse transcription-polymerase chain reaction. The demographic, clinical, and laboratory [NLR, platelet/lymphocyte ratio (PLR), complete blood count, biochemistry, and serology] data of the patients were retrospectively obtained from the hospital data management system. RESULTS NLR and fever levels were found to be higher in COVID-19 (+) cases (P=0.021, P=0.001, respectively). There was no difference between males and females with regard to COVID-19 positivity (P=0.527). Total bilirubin levels were found to be lower in COVID-19 (+) cases (P=0.040). When the ROC analysis was carried out for NLR in COVID-19 (+) cases, the AUC value was found to be 0.660 (P=0.021), sensitivity as 69.01 %, specificity as 65.40 %, LR+: 1.98 and LR- : 0.48, PPV: 80.43, and NPV: 50.00, when the NLR was ≥2.4. The risk of COVID-19 was found to be 20.3-fold greater when NLR was ≥ 2.4 in the logistic regression (P=0.007). CONCLUSION NLR is an independent predictor for the diagnosis of COVID-19. We also found that fever and total bilirubin measurements could be useful for the diagnosis of COVID-19 in this population.